The thematic groups loan-words Arabic language (Journal of Oriental Studies, 2016)
this article explores the classification of turkic loan words in arabic language. turkic loan words are given in the following thematic groups in the article: nominations of domestic belongings, food, things, metals, geographic and military terms and etc.
Keywords: turkic loan words; thematic groups